IMPROVING CYBER SECURITY ON A LIMITED BUDGET. - Brown, Richard; Ryckman, Mark (Public Management (00333611), 2010)
The article provides tips for local government managers to manage and implement cyber security measures on a limited budget. It advises managers to educate the organization about the importance of cyber security by putting policies on computer usage, installing a firewall, and regularly running anti-malware software. It also suggests managers to consider the importance back ups on computer data in a separate storage device to easily recover vital information and restore system settings.